Eastern Caribbean Currency Union : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper analyzes macroeconomic fluctuations in the Eastern Caribbean Currency Union (ECCU). The paper describes data, along with the estimation technique used to ensure stationarity of the data. The empirical regularities of macroeconomic fluctuations in the ECCU are described, examining the relationship between a set of macroeconomic time series and domestic output, for each of the six IMF members of the ECCU. The paper also explores the determinants of macroeconomic volatility in the ECCU.